Pengaruh Ukuran Serbuk Genteng Tanah Liat terhadap Penyerapan C02 pada Purifikasi Biogas - Slamet Wahyudi; Janitra Naufal Faza; Nafisah Arina Hidayati (Pusat Pengembangan, Penelitian dan Pengabdian kepada Masyarat (P4M) Politeknik Manufaktur Bandung (Polman Bandung), 2022)
Biogas is an alternative energy that has great economic value for rural communities. In practice, the CH4 biogas content is the most important part of the energy conversion process, but the impurities in the form of carbon dioxide which reduce the heating value is still large. So that efforts are needed to reduce CO2 by purification.The purpose of this study is to obtain a way of purification that improves the quality of biogas with high heating value and low CO2 impurities. The use of tile-type powder adsorbents, namely fine and coarse, which were studied at intervals of 5 and 20 minutes, for data retrieval of heat value and CO2 content. Gas Chromatography - Mass Spectrometry (GCMS) is used to test the adsorption gas content. The results showed a finer type of tile powder size gave better purification results with results at minute 5 and 20 respectively of 24.1 and 20.1% while on the type of grain size coarse at minute 5 and 20 each produced CO2 levels of 23.1 and 20.8%. Due to a decrease in CO2 levels the biogas calorific value after the highest purification is 23893 kJ/ m3 after the purification process which has resulted in a decrease in CO2 levels known during the purification process takes place the largest absorption effectiveness is 59.8% in the type of fine size within 20 minutes. The finer the size of tile powder, the heating value increases